2020
DOI: 10.38136/jgon.698866
|View full text |Cite
|
Sign up to set email alerts
|

Aile Planlaması Danışmanlık Hizmetinin Kadınların Kontraseptif Yöntem Tercihine Etkisi: Bir Tersiyer Merkez Deneyimi

Abstract: Aim: Everyone has the right to decide whether or not to have children, when to have children; to achieve effective and reliable family planning (FP) methods equally; and to receive FP counseling services. The aim of this study is to investigate the effects of women's characteristics and FP counseling service on women's choice of FP method. Material and Methods: This cross-sectional observational study was conducted with 18-45 year aged healthy volunteers who admitted to the Family Planning Unit of the Gynecolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…In a study conducted with 334 women, it was found that the IUD, condom, and combined oral contraceptive were the most common contraceptives that women thought to choose before consulting, while it was found that the preference of IUD among women increased and the preference of other methods decreased after counseling. In addition, it was determined that women thought that the most important factor affecting the choice of the method after contraception counseling was that they thought the method was safer, and 95.2% of them preferred the first method recommended by the contraception counseling staff (Kirici et al, 2020). In another study, it was found that the advice and information about the use of contraception from a general practitioner or specialist physicians have the greatest effect on women in choosing the type of contraceptives.…”
Section: Preference Of Contraceptive Methods Of Married Womenmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted with 334 women, it was found that the IUD, condom, and combined oral contraceptive were the most common contraceptives that women thought to choose before consulting, while it was found that the preference of IUD among women increased and the preference of other methods decreased after counseling. In addition, it was determined that women thought that the most important factor affecting the choice of the method after contraception counseling was that they thought the method was safer, and 95.2% of them preferred the first method recommended by the contraception counseling staff (Kirici et al, 2020). In another study, it was found that the advice and information about the use of contraception from a general practitioner or specialist physicians have the greatest effect on women in choosing the type of contraceptives.…”
Section: Preference Of Contraceptive Methods Of Married Womenmentioning
confidence: 99%
“…The availability and accessibility of contraception services facilitate the choice of contraceptive methods suitable for women's personal characteristics and health conditions (Kirici et al, 2020). In a study conducted with 334 women, it was found that the IUD, condom, and combined oral contraceptive were the most common contraceptives that women thought to choose before consulting, while it was found that the preference of IUD among women increased and the preference of other methods decreased after counseling.…”
Section: Preference Of Contraceptive Methods Of Married Womenmentioning
confidence: 99%
“…Aile planlaması danışmanlık hizmeti veren sağlık profesyonellerinin bireyler ve ailelerle etkili iletişim kurması, yöntemlerin uygun şekilde kullanılması, yan etkileri gibi bilgilerin eksiksiz şekilde anlatılması, kadınların aile planlaması yöntemlerine devam etmesinde rol oynamaktadır. 13,14 Bu nedenle kişilere ve ailelere aile planlaması danışmanlık hizmeti veren sağlık profesyonellerinin doğum kontrol yöntemleri hakkında iyi bir danışmanlık hizmeti sunmaları, yöntemlerin etkinliği, güvenilirliği ve yan etkileri konusunda güncel bilgilere sahip olmaları gerekmektedir. Kadının eğitim durumu, yaşı, sosyo-ekonomik durumu, kadınların eşlerinin aile planlamasına yönelik tutumu ve dini inanışlar gibi pek çok faktör aile planlaması yöntemlerinin kullanımını etkilemektedir.…”
Section: Introductionunclassified